Heptest-STAT, a new assay for monitoring of low-molecular-weight heparins, is not influenced by pregnancy-related changes of blood plasma - Dempfle, Carl-Erik; Zharkowa, Ulyana; Elmas, Elif; Ahmad-Nejad, Parviz; Neumaier, Michael; Borggrefe, Martin (Thrombosis and Haemostasis, 2009)
Monitoring of anti-factor Xa activity is often performed during treatment with low-molecular-weight heparins (LMWHs) in pregnancy because the anticoagulant effect may decrease as pregnancy progresses, but assays for anti-factor Xa activity are unavailable in many clinical institutions caring for pregnant women. Heptest-STAT is a new clotting assay for monitoring of LMWHs, which has been optimised for use in near-patient laboratory instrumentation. It has been suggested that monitoring of LMWHs requires the use of individual calibration curves for each LMWH.We compared the dose response of four conventional LMWHs and fondaparinux in normal plasma, and plasma from women in first, second and third trimester of pregnancy. Three concentrations of LMWHs, fondaparinux, or unfractionated heparin were added to pooled plasma samples from nonpregnant women (n=10), and pregnant women in first (n=10), second (n=10) and third (n=10) trimester of pregnancy. Heptest results are not influenced by the stage of pregnancy. In contrast, dose-related aPTT prolongation declines during pregnancy. All LMWHs tested, as well as fondaparinux, display a similar doseresponse in Heptest compared to the chromogenic anti-factor Xa assay. Heptest-STAT can be used with the same standard calibration for non-pregnant and pregnant patients and for all LMWHs under investigation, including fondparinux. No individual calibrations are necessary.
Keywords: Heparins; LMWH; pregnancy; heptest; fondaparinux; monitoring